PENGARUH INOKULASI CENDAWAN MIKORIZA ARBUSKULA DAN PHOSFAT TERHADAP PERTUMBUHAN DAN HASIL KEDELAI PADA TANAH PODSOLIK MERAH KUNING - Prabowo, Amir Hamzah; M.Sc, Ir. Elly Mustamir,; MMA, Ir. surachman, (Jurnal Sains Pertanian Equator, 2020)
This study aims to obtain the interaction between Arbuscular Mycorrhizal Fungi (AMF) and the best dose of p fertilizer on the growth and yield of soybeans in Podsolik red and yellow soils. This research was conducted in the Experimental Field of the Faculty of Agriculture, Tanjungpura University, Pontianak. This research was conducted in the Experimental Field of the Faculty of Agriculture, Tanjungpura University, Pontianak. The design used in this study was a factorial experimental method with a Completely Randomized Design (CRD) pattern with 2 treatment factors. The first factor was that mycorrhizae consisted of 2 levels of treatment namely m0 = without mycorrhizal inoculation, m1 = 20 g / polybag. The second factor is the dose of fertilizer p which consists of 4 levels of treatment, namely p1 = 100% g / polybag, p2 = 75% g / polybag, and m3 = 50% g / polybag, and p4 = 25% g / polybag so that 8 combinations are obtained treatment with 3 replications and consisted of 4 plant samples. The variables observed in this study were plant height (cm), flower age (hst), root volume (cm3), plant dry weight (g), number of pods planted (fruit), weight of 100 planted seeds (g) dry seed weight cropping (g), percentage of effective root nodules (%), and percentage of root infection (%). The results showed that the AMF inoculation treatment and the dose of P fertilizer were interactions on the root volume variable. While the CMA factor significantly affected the variable number of filled pods, weight of 100 seeds per plant, and dry weight of seeds per plant. While the dose of p fertilizer significantly affected the plant height observation variables 2 weeks after planting and root volume.